2019
DOI: 10.1111/rec.13040
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐priming seeds with cyanobacteria: effects on native plant growth and soil properties

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 46 publications
6
29
0
1
Order By: Relevance
“…mycorrhizal fungi and rhizobia; Cain et al 2008;Reece et al 2012;Evert and Eichhorn 2013). Indeed, recent work on dryland ecosystem restoration has found that in some species, including Triodia, seedling growth and establishment is enhanced with the addition of specific strains of cyanobacteria applied to the seed coats (Muñoz-Rojas et al 2018;Chua et al 2020). Consistent with this idea, we saw significantly higher emergence of T. basedowii seeds in live than sterile soil from outside the rings (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…mycorrhizal fungi and rhizobia; Cain et al 2008;Reece et al 2012;Evert and Eichhorn 2013). Indeed, recent work on dryland ecosystem restoration has found that in some species, including Triodia, seedling growth and establishment is enhanced with the addition of specific strains of cyanobacteria applied to the seed coats (Muñoz-Rojas et al 2018;Chua et al 2020). Consistent with this idea, we saw significantly higher emergence of T. basedowii seeds in live than sterile soil from outside the rings (Fig.…”
Section: Discussionsupporting
confidence: 85%
“…and Acacia spp. (Chua et al, 2019). As shown here, modified extruded seed pellets appear to be a viable method to translocate beneficial soil microbial communities from the previously removed topsoil, such as biocrust cyanobacteria, even after a short period (109 days) following inoculation.…”
Section: Implications For Large-scale Mine Rehabilitationmentioning
confidence: 58%
“…Muñoz-Rojas et al [58] highlighted the potential of cyanobacteria to increase soil functions in mine-site restoration by promoting soil carbon sequestration. Similarly, Chua et al [71] demonstrated that bio-priming native plant seeds with indigenous cyanobacteria promote seedling growth in soils commonly used in mine restoration. Moreover, these organisms can retain pollutants with high efficiency due to diverse proteins and polysaccharide receptors on their surface, acting as prominent agents in the remediation of heavy metal and hydrocarbon polluted soils [72,73].…”
Section: Cyanobacteria Applications In Ecosystem Restorationmentioning
confidence: 99%
“…Perhaps another key factor is the higher economic returns in the agricultural sector, and therefore larger investments in research development compared to that developed in natural areas. The direct delivery of cyanobacteria inoculants in soils [137][138][139], and plants/seeds [71,129,135,140] has shown positive results in ameliorating soil properties and enhancing seed germination, seedling emergence and plant growth in laboratory studies. However, successful large-scale ecosystem restoration may entail direct seeding or seedling planting [141][142][143][144].…”
Section: Challenges and Opportunities In The Application Of Cyanobacteria For Salt-affected Soils Restorationmentioning
confidence: 99%